2020
DOI: 10.1021/acs.jpcc.0c04953
|View full text |Cite
|
Sign up to set email alerts
|

Spin Properties and Electronic Structure in Organic Ternary Crystals

Abstract: In this work, the effects of the competition between donor 1 −acceptor (D 1 −A) and D 2 −A charge transfer interactions on the band structure, electronic states, and spin properties are studied in the ternary crystals D 1 −D 2 −A. Combining experimental data with theoretical calculations, it is observed that the band structure of D 1 −D 2 −A ternary crystals is not a superposition of the D 1 −A and D 2 −A binary crystal. Through changing the frequency of the incident light on ternary crystals, the dominated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Future engineering efforts will concentrate on making monomeric FPs, ensuing a fast chromophore maturation, reducing their blinking or bleaching, and increasing their brightness or color contrast upon photoswitching or photoconversion. For example, new properties/mechanisms of RFPs have recently emerged for LEA, [24f,h] mKeima, [8b,60d] and aY‐sfGFP [1h,106a] (see above). Other interesting RFPs that can motivate future ultrafast spectroscopic studies include a dark‐to‐red FP called KFP1 (Ex./Em.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future engineering efforts will concentrate on making monomeric FPs, ensuing a fast chromophore maturation, reducing their blinking or bleaching, and increasing their brightness or color contrast upon photoswitching or photoconversion. For example, new properties/mechanisms of RFPs have recently emerged for LEA, [24f,h] mKeima, [8b,60d] and aY‐sfGFP [1h,106a] (see above). Other interesting RFPs that can motivate future ultrafast spectroscopic studies include a dark‐to‐red FP called KFP1 (Ex./Em.…”
Section: Discussionmentioning
confidence: 99%
“…The large redshift was attributed to H‐bonding rearrangement near chromophores of extended conjugation [106a] or the formation of an RFP‐like chromophore (e. g., DsRed with a conjugated acylimine) [106b] . Recently, ground‐state FSRS was employed to elucidate the chromophore structure of aY‐sfGFP [1h] . By systematic spectral comparisons to model chromophores and a conventional RFP with an acylimine‐containing chromophore, an RFP‐like chromophore was shown to be absent in aY‐sfGFP due to the lack of RFP signature bands.…”
Section: Rfps With a Noncanonical Chromophorementioning
confidence: 99%
See 1 more Smart Citation
“…The strong e-p coupling allows electrons to be trapped by lattice vibrations, and the captured charge can then influence spin polarization through a spin-lattice interaction. [45] Qin et al modified the lattice configuration and phonon dependence of spin polarization by adding the third component into binary CTCs. [46] A dimerization between neighbor D and A groups was generated to induce a lattice symmetry breaking.…”
Section: Spin In Organic Ternary Cocrystalsmentioning
confidence: 99%
“…Recently, it has been reported that e‐p coupling plays a crucial role in the functioning of organic ferromagnetism. The strong e‐p coupling allows electrons to be trapped by lattice vibrations, and the captured charge can then influence spin polarization through a spin‐lattice interaction [45] . Qin et al.…”
Section: Spin In Organic Ternary Cocrystalsmentioning
confidence: 99%